Sensory Profiling and Consumer Preference of Local Ginger Chocolate Bars Using Rate-All-That-Apply - Miftakhul Firdaus; Sri Winarti; Andre Yusuf Trisna Putra (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Commercial ginger chocolate bars combine cocoa flavour with pungent, warming ginger notes, yet differences in cocoa ingredients, fat systems, milk components, ginger form, and processing can yield markedly different consumer responses. This study compared five purposively selected Indonesian commercial ginger chocolate bars, anonymized as KR, NM, MG, CU, and MJ, and integrated consumer-based Rate-All-That-Apply (RATA), preference mapping, and product-level total sugar measurement. A focus group of 10 selected participants generated a final lexicon of 19 attributes covering aroma, appearance, taste, texture/mouthfeel, and aftertaste. Eighty untrained panelists aged 20-40 years evaluated five coded samples; 0 indicated that an attribute was not perceived, whereas 1-5 represented increasing intensity, and overall liking was rated on a six-point hedonic scale. RATA data were analysed using Kruskal-Wallis and Dunn tests, principal component analysis (PCA), and preference mapping. Total sugar was determined by the anthrone method against a glucose standard coefficients across five products were treated strictly as exploratory. Eighteen attributes differed significantly, while milky aroma did not (p=0.085). PCA explained 83.39% of sensory variation. KR occupied the 80-100% overall acceptance region and was associated with sweet taste, sweet aftertaste, brown colour, and milky aroma; MJ occupied the 60-80% region and was associated with softness and melting. Among the descriptive age-group maps, panelists aged 26-35 years showed the strongest acceptance pattern, with KR and MJ both located in the 80-100% region; this subgroup was therefore highlighted in the manuscript. MG had the highest total sugar (13.02%) but was not the most preferred, illustrating that anthrone-derived sugar concentration is not equivalent to perceived sweetness or liking. The findings support product development that balances ginger identity with familiar cocoa flavour, controlled pungency, and a soft-melting texture. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production